2007
DOI: 10.1039/b701024a
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and differences on the molecular mechanism of CO oxidation on Rh(111) and bimetallic RhCu(111) surfaces

Abstract: The reaction between adsorbed CO and atomic O on various sites of Rh(111) and on the bimetallic RhCu(111) surface has been investigated by first principles density functional theory using slab models. The most likely reaction pathway for CO oxidation on Rh(111) involves probably migration of atomic oxygen from fcc to hcp sites. On the bimetallic surface the mechanism is similar, although depending on the type of bimetallic site a reduction of the energy barrier is predicted. Consequences for the NO reduction b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…41,42 The movement of the CO molecule toward the oxygen activates oxygen to the bridge site and at the TS, CO is located tilted at the off top site, while oxygen is located at the bridge site. The activation barrier associated with this TS structure is calculated as 1.28 eV, in agreement with the 1.37 eV barrier calculated in a previous theoretical publication, 43 which uses the same computational method, coverage, and activation barrier definition as in our study.…”
Section: Regime 1 (θ Totalsupporting
confidence: 88%
See 2 more Smart Citations
“…41,42 The movement of the CO molecule toward the oxygen activates oxygen to the bridge site and at the TS, CO is located tilted at the off top site, while oxygen is located at the bridge site. The activation barrier associated with this TS structure is calculated as 1.28 eV, in agreement with the 1.37 eV barrier calculated in a previous theoretical publication, 43 which uses the same computational method, coverage, and activation barrier definition as in our study.…”
Section: Regime 1 (θ Totalsupporting
confidence: 88%
“…O theoretically through DFT calculations. 31,[39][40][41][42][43] The major outcomes of the experimental studies have been the establishment of the Langmuir-Hinshelwood mechanism of the reaction, 37 observance of different reactivity regimes at different reactant coverage, 19,[32][33][34] and more importantly structure sensitivity for the reaction. 12,13,35,36,38 Although the earlier studies have suggested that the reaction was insensitive to surface structure, i.e., identical kinetic parameters were obtained on different surfaces, 12,35 later it has been proposed that the so-called "structure insensitivity" was only observed when the surfaces were covered mainly by CO, indicating that the reaction is structure sensitive for oxygen-rich surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transition from sp 3 to sp 2 is easier than the reverse, which results the common seen form of carbon as graphite. Once the transition from sp 2 to sp 3 is made possible, the final structure will mostly be in diamond form for its more stable configuration than the lonsdaleite C. 21 This could be the reason why carbon in lonsdaleite form is so rarely seen than graphite and diamond in nature.…”
Section: Orbital Hybridization and Materials Propertiesmentioning
confidence: 99%
“…20 The molecular mechanism of CO oxidation on Rh (111) and RhCu (111) surfaces was suggested through DFT calculation within the generalized gradient approximation. 21 Kacprzak et al studied the bond change in the formation of hydrogen peroxide on gold clusters by DFT Car-Parrinello molecular dynamics simulation. 22 The lonsdaleite structure is the one component analogue of the wurtzite structure with the crystallographic symmetry of P6 3 /mmc.…”
Section: Introductionmentioning
confidence: 99%